Netwerk/ center for contemporary art : Annual 2006. - D'Hondt, Roger; Devillez, Virginie; Franck, Philippe; Gielen, Denis; Klimová, Barbora; Kwakkenbos, Lars; Poitevin, Jean-Louis; Stevenheydens, Ive (Aalst : Netwerk / centrum voor hedendaagse kunst Aalst, 2007)
Abäke ; Behr, Bernd ; Brinkmann, Simona ; Cain, Ben ; Cobbing, William ; Cohen, Lynne ; Danckaert, Bert ; Degrève, Maria ; Dementieva, Alexandra ; Denicolai, Simona ; Denys, Francis ; Dockx, Nico ; Goldenberg, David ; Guns, Patrick ; Jacobs, Aernoudt ; Kelly, Conor ; Vanden Meersch, Els ; Moti, Melvin ; Naveriani, Maia ; New Reform Archive ; Nys, Sophie ; Posehn, Kristin ; Provoost, Ivo ; Reynolds, Audrey ; Satom, Saki ; Schepens, Steve ; Somerlinck, Jozef
Engels
Nederlands
kunstcatalogus
Keywords: Netwerk